RANCANG BANGUN MODUL PRAKTIKUM APLIKASI OP-AMP BERBASIS IC 741 DAN IC 301 - Wahyu Rizal Nugraha; Tan Suryani Sollu; Ardi Amir (Foristek, 2019)
The objective of this research is to design and create a practicum application of op-amp (operational amplifier) based on IC 741 and IC 301. By adding the components R (Resistor) C (Capacitor) IC op-amp can be applied into several series. In this practical tool there are several modules of the experiment such as multiplier, the enumerator, deduction, comparison, integrator, differentiators. This tool also equipped with a series active filter such as low pass filter, high pass filter, band pass filter and band stop filter. This practical tools requires some tool support in the form of power supply as an input voltage, a function generator to generate signals with different shapes as desired in accordance with the requirements when the practical activities and the oscilloscope as a tool of reader input waveform and the output of the circuit that exist in practical tools. Practical activities and oscilloscopes as input and output wave reader from the circuits in the practicum